PENGARUH PERENCANAAN ANGGARAN, KUALITAS SUMBER DAYA MANUSIA, DAN PENCATATAN ADMINISTRASI TERHADAP KETERLAMBATAN PENYERAPAN ANGGARAN PADA ORGANISASI PERANGKAT DAERAH DI PEMERINTAH PROVINSI RIAU - Noraimah Noraimah; Restu Agusti; Supriono Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted on 37 regional organization of Riau Province. This research is included in quantitative research. The type of data used is the primary data. Sampling was done by Purposive Sampling method. This data was analyzed using multiple linear regression that was processed with the help of SPSS program. This study aims to determine the effect of Budget Planning, Human Resource Quality, and Administration Record of Delayed Budget Absorption organization of Riau Province. The main issues that will be explained by the researcher are as follows: to see how big influence between independent variable with dependent variable. The results showed that Budget Planning, Human Resources Quality, and Administration Registration have an effect on Delay of Absorption of Budget. So the conclusion of this research is all hypothesis presented acceptable.Keywords : Budget Absorption Delay, Budget Planning, Human Resource Quality, Administrative Recording